Russia' banking sector transition: Where to? - Andrei V. Vernikov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
This paper applies an analytical paradigm of institutional economics to the transition of the Russian banking sector, focusing on the interplay between ownership change and institutional change. We find that the state's withdrawal from commercial banking has been inconsistent and limited in scope.To this day, core banks have yet to be privatized and the state has made a comeback as owner of the dominant market participants.We also look at the new institutions imported into Russia to regulate banking and finance, including rule of law, competition, deposit insurance, bankruptcy, and corporate governance.The unfortunate combination of this new institutional overlay and traditional local norms of behavior have brought Russia to an impasse - the banking sector's ownership structure hinders further advancement of market institutions. Indeed, we may now be witnessing is a retreat from the original market-based goals of transition.
URN:NBN:fi:bof-201408072176
Keywords: G21; G28; P34; P37; 330; banking sector reform; privatization; Russia; economic transition; institutional economics